(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Deli Sisig, located in Barangay 178 Camarin, Caloocan City, is a food business proposed by nine people who conceptualized the ideas and strategies to forecast the feasibility of this business. The researchers came up with the idea of this business corresponding to the same vibe of eating sisig during break time way back in the first year of college up to the present. This has become the favourite comfort food of the researchers. Deli Sisig will soon be open with a beginning capital of forty-five thousand for the starting year of operation. It is much different from its competitors, who could be more expansive in accommodating customers by offering take-out orders only. Yet, Deli Sisig sees the opportunity to make it unique from them. Aside from offering take-out orders, it also offers dine-in services for the customers. Moreover, it has various sisig offers on the menu at a lower price than the competitors, which can be one of the business’s strengths. Deli Sisig targets all the citizens around the location, even the people outside the vicinity, and all the marketers who pass around to buy their goods because the chosen location is near the wet and dry market, which is an opportunity for the researchers for the business operation.